1980
DOI: 10.1542/peds.65.5.995
|View full text |Cite
|
Sign up to set email alerts
|

Coronal Craniostenosis: Fetal Head Constraint as One Possible Cause

Abstract: A retrospective study of 11 instances of idiopathic coronal craniostenosis in otherwise normal children revealed that early lightening, prolonged moderate to severe pelvic discomfort late in pregnancy, and/or an abnormal fetal lie were unusual gestational features indicative of intrauterine constraint for eight of these patients. The impression of unusual constraint in utero was futher implied by finding associated positional foot deformities in four of these latter eight children. We hypothesize that prolonge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 87 publications
(10 citation statements)
references
References 0 publications
1
9
0
Order By: Relevance
“…Third-trimester testicular descent may also be related to fetal position because it alleg-edly correlates well with handedness (Chang et al, 1960; but see Antliff & Shampo, 1959). (Asymmetries in testicular weight may on the other hand be more related to a lateralized embryonic growth gradient [Mittwoch, 1975 ], as they correlate poorly with the side of greatest descent [Chang et al,I960]) Some severe limb and craniofacial abnormalities can also be traced to uterine constraints (Graham et al, 1980;Muakkassa et al, 1984;Rischbieth, 1963), because they are more common in males (whose head circumference is larger) and in fetuses born to women with small uteruses. Most craniofacial asymmetries probably originate during the first trimester, however (see Trenouth, 1985).…”
Section: Sources Of Prenatal Lateralizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Third-trimester testicular descent may also be related to fetal position because it alleg-edly correlates well with handedness (Chang et al, 1960; but see Antliff & Shampo, 1959). (Asymmetries in testicular weight may on the other hand be more related to a lateralized embryonic growth gradient [Mittwoch, 1975 ], as they correlate poorly with the side of greatest descent [Chang et al,I960]) Some severe limb and craniofacial abnormalities can also be traced to uterine constraints (Graham et al, 1980;Muakkassa et al, 1984;Rischbieth, 1963), because they are more common in males (whose head circumference is larger) and in fetuses born to women with small uteruses. Most craniofacial asymmetries probably originate during the first trimester, however (see Trenouth, 1985).…”
Section: Sources Of Prenatal Lateralizationmentioning
confidence: 99%
“…Given that leftward positioning during the final trimester prevails for about two thirds of fetuses, many “natural” asymmetries that approximate a 2:1 ratio and conceivably emerge during the final trimester may either directly or indirectly result from this influence. Besides the behavioral asymmetries that will be reviewed in subsequent sections, these include (a) lateralization of various neuromuscular diseases (e.g., neuralgic amyotrophy and laryngeal palsy), electroencephalographic (EEG) abnormalities, neoplasias, and other pathological disorders (Geschwind & Galaburda, 1985c; Greene, 1980; Paolozzi, 1970); (b) testicular asymmetry, expressed in a larger weight on the right side and a greater descent on the left (Antliff & Shampo, 1959; Chang, Hsu, Chan, & Chan, 1960; Mittwoch, 1975), and (c) lateralization of major craniofacial and limb malformations (Fujino et al, 1963; Gorlin, Pindborg, & Cohen, 1982; Graham, Badura, & Smith, 1980; Muakkassa et al, 1984; Rischbieth, 1963; Schnall & Smith, 1974; Tisserand, 1944; Yorita & Melnick, 1988).…”
Section: Sources Of Prenatal Lateralizationmentioning
confidence: 99%
“…70−72 Conversely, the presence of external pathological forces can also have a major impact on skull development. For example, primiparity, 17 multiple births, 73 low pelvic station, 41 and late-term pregnancies 74 have all been associated with the development of SSC.…”
Section: Acs Biomaterials Science and Engineeringmentioning
confidence: 99%
“…For over two decades, it has been suggested that in utero head constraint is associated with an increased incidence of premature calvarial suture fusion. , Previous studies have shown that early descent into the pelvis, primiparity and other forms of fetal constraint have been implicated as causing both metopic and sagittal synostosis. ,,, The proposed pathogenesis in these cases is that compression of the calvaria leads to reduced strain, at the osteogenic fronts and ultimately early suture fusion. These clinical examples are consistent with animal models of fetal constraint wherein cervical ligatures were used to prolong gestation resulting in craniosynostosis .…”
Section: Developmental Biomechanics Of Suture Formationmentioning
confidence: 99%
See 1 more Smart Citation